Neuro-Behavioral Status and the Hippocampal Expression of Metabolic Associated Genes in Wild-Type Rat Following a Ketogenic Diet - Ling, Ya; Wang, Dan-dan; Sun, Yu-xiao; Zhao, Dong-jing; Ni, Hong (Frontiers in Neurology, 2019)
While a ketogenic diet (KD) is a well-established therapy for medically intractable epilepsy, clinical evidence of relevant adverse events of a KD has also been reported. We asked whether this kind of diet would have deleterious effects on wild-type brain function by evaluating KD-induced biochemical changes in the hippocampus as well as neurobehavioral changes occurring in wild-type rats. Fifty-four Sprague-Dawley rats were randomly assigned to three groups on postnatal day 28 (P28): wild-type rats fed with a KD qd (daily for 4 weeks, KD) or qod (every other day for 4 weeks, KOD), and wild-type rats fed with standard normal laboratory diet (ND). Neurobehavioral changes were observed on P35, P42, and P49. The hippocampal mossy fiber sprouting, the expression levels of zinc transporters (ZnTs) and lipid metabolism related genes were detected by Timm staining, RT-qPCR and western blot analysis, respectively, on P58. The KD-treated KOD and KD groups showed a significant delay of negative geotaxis reflex on P35, but not on P42 or P49. In the open field test, daily KD treatment only led to a reduction in exploratory activity and increased grooming times but induced no significant changes in the scores of vertical activity or delay time. KD qod treated rats (KOD) displayed a slight delay in the place navigation test on P35 compared with the KD group. There were no significant differences in Timm staining among the three groups. In parallel with these changes, KD treatment (both KD and KOD) induced significantly downregulated mRNA levels of Apoa1, Pdk4, and upregulated expression of ApoE, ANXN7, and cPLA2 in the hippocampus when compared with the ND group (except in the case of ApoE in the KOD group). Notably, both the mRNA and protein levels of cPLA2 in the KOD rats were significantly downregulated compared with the KD group but still markedly higher than in the ND group. No significant difference was found in ZnTs among the three groups. Our data suggest that early-life KD can provoke minor neurobehavioral effects in particular a delay in negative geotaxis reflex and an increase in grooming activity. The hippocampal lipid metabolism signaling pathway, especially cPLA2, may be the target of the protective effect of KD on long-term brain injury after developmental seizures.